Prostate microcalcification crystallography as a marker of pathology - Gosling, Sarah; Arnold, Emily; Adams, Lois; Cool, Paul; Geraki, Kalotina; Kitchen, Mark O.; Lyburn, Iain D.; Rogers, Keith; Snow, Tim; Stone, Nick; Greenwood, Charlene (Springer, 2025)
Prostate cancer remains the most common male cancer; however, treatment regimens remain unclear in some cases due to a lack of agreement in current testing methods. Therefore, there is an increasing need to identify novel biomarkers to better counsel patients about their treatment options. Microcalcifications offer one such avenue of exploration. Microfocus spectroscopy at the i18 beamline at Diamond Light Source was utilised to measure X-ray diffraction and fluorescence maps of calcifications in 10 µm thick formalin fixed paraffin embedded prostate sections. Calcifications predominantly consisted of hydroxyapatite (HAP) and whitlockite (WH). Kendall’s Tau statistics showed weak correlations of ‘a’ and ‘c’ lattice parameters in HAP with GG (rτ = − 0.323, p = 3.43 × 10–4 and rτ = 0.227, p = 0.011 respectively), and a negative correlation of relative zinc levels in soft tissue (rτ = − 0.240, p = 0.022) with GG. Negative correlations of the HAP ‘a’ axis (rτ = − 0.284, p = 2.17 × 10–3) and WH ‘c’ axis (rτ = − 0.543, p = 2.83 × 10–4) with pathological stage were also demonstrated. Prostate calcification chemistry has been revealed for the first time to correlate with clinical markers, highlighting the potential of calcifications as biomarkers of prostate cancer.
Keywords: Prostate cancer; Calcification; Biomarkers; 32 Biomedical and Clinical Sciences; 3211 Oncology and Carcinogenesis; Cancer; Urologic Diseases; Aging; 4.1 Discovery and preclinical testing of markers and technologies; Biomarkers; Calcification; Male; Humans; Prostatic Neoplasms; Calcinosis; Prostate; X-Ray Diffraction; Durapatite; Biomarkers, Tumor